Structural Characterization of a Gold/Serum Albumin Complex - Alessandro Pratesi; Damiano Cirri; Dolores Fregona; Giarita Ferraro; Anna Giorgio; Antonello Merlino; Luigi Messori (2019)
The medicinal gold(III) dithiocarbamato complex AuL12 forms a stable adduct with bovine serum albumin. The crystal structure reveals that a single gold(I) center is bound to Cys34, with the dithiocarbamato ligand being released. To the best of our knowledge, this is the first structure for a gold adduct of serum albumin.